Quality control of kremes noodle products based on food safety aspects with six sigma and swot methods - Ariyanto, M Diky; Wahyuni, Hana Catur (SEAN Institute, 2024)
At this time food safety problems often occur in the management of the production process from internal and external factors, this occurs because the quality of the production is not good enough to affect the quality of the product. Aims to improve quality in the production process of Kremes Noodles to determine critical to quality, determine the quality level of noodle products, and develop strategies to improve the quality of Kremes Noodle products. So by using the six sigma method which has the steps of Defining, Measuring, Analyzing, Improving, and Controlling. To strengthen the strategy in the improve stage, this is done using a SWOT analysis. In this study, there are 5 types of errors that have an impact on product quality and one of the strategies used is to carry out inspections before the process starts and monitoring during the process.